Phytochemical Content and Antioxidant Activity of Sphagnum spp: From Sicike-Cike Nature Tourism Park, North Sumatra - Sinta R Pardosi; Etti Sartina Siregar; Isnaini Nurwahyuni (Eduvest - Journal of Universal Studies, 2025)
Sphagnum, which belongs to the Bryophyta moss group, is known as peat moss due to its primary role in the formation and accumulation of peat. Studies on the antioxidant potential of Sphagnum moss in Indonesia have not been reported. Therefore, research on the antioxidant activity potential in Sicike-cike Nature Tourism Park (TWA) is necessary. This study aims to analyze the phytochemical composition and antioxidant activity of ethanol extracts from four species of Sphagnum: S. cuspidatum, S. junghianum, S. palustre, and S. perichatiale. Extraction was carried out using the maceration method, resulting in dark green solid ethanol extracts. The solid extracts were analyzed for secondary metabolites using phytochemical screening. Antioxidant activity was determined using the DPPH method. The phytochemical screening results of the four ethanol extracts of Sphagnum showed the presence of alkaloids, flavonoids, tannins, saponins, terpenoids, and glycosides in varying compositions among the species. Meanwhile, the IC50 values ranged from 123.6347 µg/mL to 666.1506 µg/mL. S. perichatiale showed the highest antioxidant activity, indicating its potential as a natural antioxidant source. In contrast, S. cuspidatum exhibited the lowest antioxidant activity. These findings highlight the importance of Sphagnum as a valuable source of bioactive compounds with potential applications in pharmaceuticals and cosmetics.